FUNGSI MUSIK DALAM RITUAL BALALAK DI DESA MONTERADO KECAMATAN MONTERADO KABUPATEN BENGKAYANG - Imanuel Imanuel; Ismunandar Ismunandar; Asfar Munir (Universitas Tanjungpura, 2019)
Abstract This rescarh was based to know presentation and function Balalak music on celebration at Monterado village, Monterado district, Bengkayang district,the purpose of this study was how form presentation and function Balalak music, celebration at Monterado village ,Monterado sub- district, Bengkayang district. This research used was desctripve methodand the research reom used is qualative research. Sources of datain this study some interviewsa and relevan sources about the presentation and funcation Balalak music at Monterado village, Monterado sub district Bengkayang district. Data collection techsuch as observation interviews study literature and documentation. Technique such observation to test the validity of data used was sources triangulation, triangulation techniqueand lengthen observation data analysis techniques in thi study used was inreactive data analysis to include data presentation and deduce. Basd on data analysis it was can to concludemusik on ritual Balalak as rite of passage Balalak the accompanist, communication and entertaimen. From presentation and function Balalak music at Monterado village, Monterado sub-district, Bengkayang district. Is instrument, onstage, makeup, soundsytem and presentation order. These results can applied to the community,in the was Borne. Keywords: Balalak Music Function and Form of Presentation